2021
DOI: 10.5115/acb.21.086
|View full text |Cite
|
Sign up to set email alerts
|

Bicipital origin and the course of the plantaris muscle

Abstract: The plantaris muscle (PM) has a small fusiform muscle belly and a long slender tendon sandwiched between the soleus (SM) and gastrocnemius muscle (GM). During routine dissection for research, an additional PM in the popliteal region of a 75-year-old Korean female was discovered. Two distinct PMs were present, the superior PM (sPM) and inferior PM (iPM). While the sPM originates from the lower lateral supracondylar ridge and the knee capsule, the iPM originates from the femoral condyle and sPM tendon splitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…17 This is influenced by the medial and lateral angles of the plantar arch in girls greater than in boys. 18,19 Based on research conducted by Xu et al, children of the male sex have a higher possibility of flat feet than girls. 6 Supported by research, Abich et al found that children with the male sex have 1.5 times the likelihood of having flat feet than girls.…”
Section: Discussionmentioning
confidence: 99%
“…17 This is influenced by the medial and lateral angles of the plantar arch in girls greater than in boys. 18,19 Based on research conducted by Xu et al, children of the male sex have a higher possibility of flat feet than girls. 6 Supported by research, Abich et al found that children with the male sex have 1.5 times the likelihood of having flat feet than girls.…”
Section: Discussionmentioning
confidence: 99%